The rise of 3D bioprinting advancements in modeling neurodegenerative diseases - Lucia Iafrate; Gianluca Cidonio (Ibrain)
Abstract Neurodegenerative diseases (NDs) are disorders that drastically alter the physiological functioning of neurons in the brain. These processes are often accompanied by abnormal protein aggregates that alter the physical and chemical properties of brain tissue and peripheral nerves. The causes of NDs are complex, involving genetic factors, neuroinflammation, oxidative stress, environmental influences, and lifestyle, while symptoms and progression vary significantly based on the mechanisms of cell death. Currently, no definitive treatment exists for NDs, as the underlying degenerative processes remain poorly understood. Existing therapies focus on symptom alleviation but are insufficient to halt or prevent disease progression. This highlights the urgent need for strategies that mimic the pathophysiology of NDs, facilitating deeper insights and the development of effective treatments. Conventional in vitro and in vivo models attempt to replicate NDs but often fail to capture the physiological complexity of nervous tissue and its interactions. In this context, 3D microfluidic bioprinting emerges as a transformative technology. By enabling precise deposition of cells and biomaterials, it allows the creation of in vitro models with a high degree of structural and functional complexity. These advancements provide a valuable platform for faithfully modeling NDs, bridging critical gaps in our understanding, and paving the way toward innovative therapeutic approaches.